A geopolymer-stabilized recycled aggregate road base material and preparation method thereof

By using geopolymers to stabilize the regenerated aggregate road base material in cement-stabilized gravel base material, and using interface exciters and nanocrystalline agents to stimulate the gelling activity of the regenerated aggregate surfactant, the problems of cement-stabilized gravel base material in carbon emissions and raw material supply are solved, the interface strength and crack resistance are improved, and the low-cost and environmentally friendly highway base material is achieved.

CN119176698BActive Publication Date: 2025-03-07HEBEI PROVINCIAL COMM PLANNING & DESIGN INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411689017.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing cement-stabilized gravel base materials have problems in carbon emissions and raw material supply, and the surface impurities and high water absorption of brick-concrete recycled aggregates lead to low interface strength, affecting construction quality.

Method used

The geopolymer is used to stabilize the regenerated aggregate road base material, and the cementitious regenerated aggregate, fly ash, slag powder, steel slag powder, calcium carbide slag, sodium metasilicate pentahydrate, sodium silicate, sodium hydroxide and interface exciter are used to stimulate the gelation activity of the regenerated aggregate surfactant by using the interface exciter and nanocrystalline nucleation agent to improve the interface strength.

Benefits of technology

It has achieved a complete replacement of cement materials, improved interface strength and crack resistance, reduced drying shrinkage and carbon emissions, and has the advantages of low cost and environmental protection. It is suitable for low-carbon construction of highways.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176698B_ABST
    Figure CN119176698B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of resource utilization of industrial solid waste, and specifically relates to a geopolymer stabilized recycled aggregate road base material and a preparation method. The present invention uses industrial solid waste slag powder, fly ash, steel slag powder, and carbide slag to prepare geopolymer cementitious materials, uses brick-concrete recycled aggregate as aggregate, uses sodium metasilicate pentahydrate, sodium silicate, and sodium hydroxide as alkali activators, combines interface activators and nanocrystalline nucleating agents, proposes a surface activation and secondary activation method for brick-concrete recycled aggregate, and prepares a road base material that fully utilizes solid waste, has high interface strength, good crack resistance, is economical and environmentally friendly, has high mechanical strength, and has low drying shrinkage. It can reduce the carbon emissions and material costs of semi-rigid base construction, ensure the construction quality of brick-concrete recycled aggregate utilization, and effectively absorb a large amount of industrial solid waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of resource utilization of industrial solid waste, and specifically relates to a geopolymer stabilized recycled aggregate road base material and a preparation method thereof. Background Art

[0002] As a semi-rigid base material, cement-stabilized crushed stone is widely used in highways of all levels in my country. It has the advantages of excellent performance and simple process. However, affected by the dual carbon strategy, the supply of cement and natural aggregate, the raw materials of cement-stabilized crushed stone, is seriously insufficient. The carbon emissions of cement and natural aggregate account for more than 50% of the total carbon emissions of highway construction. As a high-carbon emission building material, the production of 1 ton of cement will release nearly 1 ton of CO 2 , affected by the "carbon peak and carbon neutrality" strategy, prices continue to rise and production capacity is limited. At the same time, the excavation of stone factories is severely restricted, resulting in a serious shortage of natural aggregates for engineering, which has led to an irreconcilable contradiction between engineering demand and natural aggregate supply.

[0003] In industrial production, a large amount of industrial waste needs to be effectively treated, otherwise it will cause environmental pollution. Therefore, there is an urgent need for a clean, green, and highly efficient semi-rigid base material that utilizes solid waste materials. Highway reconstruction and expansion and building demolition will generate a large amount of construction waste. After processing and shaping, bricks and concrete recycled aggregates (hereinafter referred to as brick-concrete recycled aggregates) can be obtained to replace natural aggregates. However, the surface of brick-concrete recycled aggregates has many impurities and high water absorption, resulting in extremely low mortar-bone interface strength between the binder and the recycled aggregate, resulting in low mechanical strength and large drying shrinkage of the pavement base material with brick-concrete recycled aggregate as the main aggregate, especially low splitting strength, resulting in severe cracking on the base surface after construction, seriously affecting the construction quality.

[0004] Therefore, the present invention provides a geopolymer-stabilized recycled aggregate road base material and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a geopolymer-stabilized recycled aggregate road base material and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] A geopolymer stabilized recycled aggregate road base material comprises the following components by weight: 100 parts of brick-concrete recycled aggregate, 1.0-2.5 parts of fly ash, 1.0-2.0 parts of slag powder, 1.0-1.5 parts of steel slag powder, 0.5-1.5 parts of carbide slag, 0.3-1.0 parts of sodium metasilicate pentahydrate, 0.2-1.2 parts of sodium silicate, 0.2-1.0 parts of sodium hydroxide, 4.5-6.5 parts of water, 0.05-0.3 parts of interface activator and 0.1-0.3 parts of nanocrystalline nucleating agent.

[0008] Furthermore, the synthetic gradation of the brick-concrete recycled aggregate is as follows: the percentage passing through the sieve hole size of 19 mm is 100%, the percentage passing through the sieve hole size of 16 mm is 88-93%, the percentage passing through the sieve hole size of 13.2 mm is 76-86%, the percentage passing through the sieve hole size of 9.5 mm is 59-72%, the percentage passing through the sieve hole size of 4.75 mm is 35-45%, the percentage passing through the sieve hole size of 2.36 mm is 22-31%, the percentage passing through the sieve hole size of 1.18 mm is 13-22%, the percentage passing through the sieve hole size of 0.6 mm is 8-15%, the percentage passing through the sieve hole size of 0.3 mm is 5-10%, the percentage passing through the sieve hole size of 0.15 mm is 3-7%, and the percentage passing through the sieve hole size of 0.075 mm is 2-5%.

[0009] Furthermore, the fly ash is low-calcium secondary fly ash, SiO 2 、Al 2 O 3 , Fe 2 O 3 The total mass is not less than 70%, the mass fraction of free calcium oxide (f-CaO) is not more than 1.0%, and the mass fraction of sulfur trioxide (SO 3 ) mass fraction is not more than 3.5%, and the passing rate of 45μm square hole sieve is not less than 70%.

[0010] Furthermore, the slag powder is S95 grade slag powder with a specific surface area of ​​not less than 400m 2 / kg, 7d activity index not less than 70%, sulfur trioxide (SO 3 ) mass fraction is not more than 4.0%.

[0011] Furthermore, the specific surface area of ​​the steel slag powder is not less than 350 m 2 / kg.

[0012] Furthermore, the effective calcium and magnesium content in the carbide slag is not less than 55%, and the passing rate of a 0.15 mm square hole sieve is not less than 95%.

[0013] Furthermore, the sodium metasilicate pentahydrate has a purity of 99% and a pH value (1% aqueous solution) of 12.5±0.1.

[0014] Furthermore, the sodium silicate is solid sodium silicate in powder form with a purity of 99%.

[0015] Furthermore, the interface activator is an alcoholamine material, specifically one of triethanolamine, triisopropanolamine, diethanol monoisopropanolamine, and monoisopropanolamine.

[0016] Furthermore, the nano-crystal nucleating agent is a nano-CSH crystal nucleating solution.

[0017] A method for preparing a geopolymer-stabilized recycled aggregate road base material comprises the following steps:

[0018] Step S1: dissolving the interface activator and the nanocrystalline nucleating agent in 2 / 5 of the mass fraction of water, stirring evenly to obtain an activator solution, pouring it into the brick-concrete recycled aggregate, and soaking it for 2-3 hours to obtain the impregnated brick-concrete recycled aggregate;

[0019] Step S2: dissolving sodium metasilicate pentahydrate, sodium silicate and sodium hydroxide in the remaining mass fraction of water to prepare an activator solution;

[0020] Step S3: Add 3 / 10 mass fraction of the activator solution to the soaked brick-concrete recycled aggregate for the first time and stir for 1-3 minutes, then add a mixture of fly ash, steel slag powder, slag powder and carbide slag, stir evenly, and then add the remaining mass fraction of the activating solution for a second time and stir for 2-5 minutes to obtain a geopolymer stabilized recycled aggregate road base material.

[0021] Furthermore, the brick-concrete recycled aggregate is modified, and the specific process is as follows:

[0022] The brick-concrete recycled aggregate and the silane coupling agent solution are mixed evenly, reacted at 40-50°C for 3-5 hours, taken out, added into the modified silicone resin, reacted at 30-40°C for 10-12 hours, taken out, and air-dried at 100-110°C for 8-10 hours to obtain the modified brick-concrete recycled aggregate.

[0023] Furthermore, the silane coupling agent solution includes the following components by weight: 20-30 parts of γ-glycidyloxypropyltrimethoxysilane, 300-500 parts of ethanol, and 100-200 parts of deionized water.

[0024] Furthermore, the mass of the modified silicone resin is 3-5 times the mass of the brick-concrete recycled aggregate.

[0025] Furthermore, the preparation method of the modified silicone resin is as follows:

[0026] Step A: Under nitrogen protection, octamethylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane and trifluoropropyltrimethylcyclotrisiloxane are mixed evenly, heated to 100-110°C, tetramethylammonium hydroxide and deionized water are added and mixed evenly, reacted for 3-5h, and then heated to 145-150°C, kept warm for 2-3h, filtered and dried to obtain terminal hydroxyl fluorinated organosilicon;

[0027] Step B: Mix polyvinyl alcohol and deionized water at 80-90° C., cool to 60-70° C., add terminal hydroxyl fluorinated silicone and dibutyltin dilaurate, react for 2-4 hours, filter and dry to obtain a modified polymer;

[0028] Step C: Under nitrogen protection, ultrasonically dispersing nanocellulose in N,N-dimethylacetamide solution containing lithium chloride to obtain a nanocellulose solution, heating the solution to 50-60° C., adding oleic acid chloride, reacting for 3-5 hours, filtering, washing, and freeze-drying to obtain modified nanocellulose;

[0029] Step D: uniformly mix the modified polymer, acrylamide, octadecyl methacrylate, methyl methacrylate, deionized water and azobisisobutyronitrile, add a mixed solution of modified nanocellulose, deionized water and a surfactant, and react at 70-80° C. for 6-8 hours to obtain a modified silicone resin.

[0030] In the above technical scheme, deionized water is used as a capping agent and tetramethylammonium hydroxide is used as a catalyst. Octamethylcyclotetrasiloxane, trifluoropropyltrimethylcyclotrisiloxane and pentamethylpentavinylcyclopentasiloxane are reacted to introduce double bonds to obtain terminal hydroxyl fluorinated silicone, which also contains vinyl and has high viscosity and good hydrophobic properties. Polyvinyl alcohol is a polyhydroxy polymer containing a large number of active hydroxyl groups in the molecule. Under the catalytic action of dibutyltin dilaurate, polyvinyl alcohol and -OH in the terminal hydroxyl fluorinated silicone undergo dehydration condensation, and a side chain with a hydrophobic Si-O bond is introduced into the long chain of polyvinyl alcohol, further improving the waterproof performance of the material. Nanocellulose is used as a reinforcing material, and oleic acid chloride is used to perform surface hydrophobic modification on nanocellulose to obtain modified nanocellulose with double bond groups on the surface. Finally, under the action of an initiator, the modified polymer, acrylamide, octadecyl methacrylate, and methyl methacrylate react with the modified nanocellulose to obtain a hydrophobic modified silicone resin containing amino groups.

[0031] Furthermore, in the step A, the mass ratio of octamethylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane and trifluoropropyltrimethylcyclotrisiloxane is 1:(1.0-1.2):(2.0-2.2).

[0032] Furthermore, in step A, the mass of tetramethylammonium hydroxide is 0.03-0.05% of the mass of trifluoropropyltrimethylcyclotrisiloxane, and the mass of deionized water is 0.1-0.3% of the mass of trifluoropropyltrimethylcyclotrisiloxane.

[0033] Furthermore, in step B, the mass ratio of polyvinyl alcohol, deionized water, terminal hydroxyl fluorinated silicone and dibutyltin dilaurate is 1:(10-12):(1-2):(0.03-0.05).

[0034] Furthermore, in step C, the content of lithium chloride in the N,N-dimethylacetamide solution is 5-7wt%, the concentration of the nanocellulose solution is 2-5wt%, and the mass of oleic acid chloride is 2-4 times the mass of nanocellulose.

[0035] Furthermore, in step D, the mass ratio of the modified polymer, acrylamide, octadecyl methacrylate, methyl methacrylate, deionized water and azobisisobutyronitrile is 1:(1.5-2.5):(1-2):(2-3):(10-15):(0.1-0.3).

[0036] Furthermore, in the step D, the mass ratio of the modified polymer to the modified nanocellulose is 1:(0.3-0.5), and the mass ratio of the modified nanocellulose, deionized water and the surfactant is 1:(15-30):(0.5-0.8).

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. A geopolymer-stabilized recycled aggregate road base material and a preparation method of the present invention utilize the alkali-excitation reaction characteristics of geopolymers and the secondary excitation effect of the interface to stimulate the gelling activity of the surface active substances of the recycled aggregate and the industrial solid wastes of fly ash, steel slag powder, slag powder, and carbide slag. It can completely replace high-energy consumption and high-pollution cement materials and can replace commonly used cement-stabilized crushed stone. It has the advantages of high interface strength, good crack resistance, fast early strength growth, small drying shrinkage, low material cost, small carbon emissions, and all-solid waste low-carbon construction, which helps the low-carbon construction of highways;

[0039] It ensures the application effect of brick-concrete recycled aggregates in road base during highway reconstruction and expansion and building demolition, effectively absorbs industrial solid waste materials, alleviates the pressure of solid waste storage, reduces the use of cement materials and natural aggregates, reduces greenhouse gas emissions, and reduces project costs, which has important environmental, economic and social benefits.

[0040] 2. The present invention provides a geopolymer stabilized recycled aggregate road base material and a preparation method. By adding an interface stimulant and a nanocrystalline nucleating agent during the simmering process, the gelling activity of the surface active substances of the recycled aggregate is stimulated through secondary excitation at the slurry-bone interface, thereby improving the surface microstructure of the recycled aggregate, improving the excitation effect and interface strength of the interface transition zone between the geopolymer and the brick-concrete recycled aggregate, improving the compressive strength and crack resistance of the stabilized material, and reducing drying shrinkage, thereby reducing the risk of shrinkage cracking of the base layer and reflection of cracking on the road surface.

[0041] 3. A geopolymer stabilized recycled aggregate road base material and preparation method of the present invention, wherein the brick-concrete recycled aggregate is modified by a silane coupling agent (γ-glycidyloxypropyl trimethoxysilane) and a modified silicone resin to prepare a surface hydrophobic brick-concrete recycled aggregate; γ-glycidyloxypropyl trimethoxysilane is used as a medium between the inorganic material and the silicone resin, and after the silane coupling agent is hydrolyzed, the alkoxy group at one end is hydrolyzed into a silanol group, which can undergo a polycondensation reaction with the hydroxyl group on the surface of the brick-concrete recycled aggregate to form a strong hydrogen bond and a covalent bond; at the same time, the epoxy group at the other end can react with the amino group in the modified silicone resin to form a cross-linked structure, further improving the binding force between the modified silicone and the brick-concrete recycled aggregate. This modification treatment not only effectively reduces the water absorption rate of the recycled aggregate and reduces the influence of surface impurities, but also significantly improves the mechanical strength of the road base material with the brick-concrete recycled aggregate as the main component, thereby improving the construction quality and the service life of the road. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0043] In the attached picture: Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] It should be noted that the purchasers of all raw materials involved in the present invention include, without any special restrictions, illustratively:

[0046] Brick-concrete recycled aggregate: from construction waste treatment plant; fly ash: from Hebei Tonghua Highway Materials Co., Ltd.; steel slag powder: from Hebei Tonghua Highway Materials Co., Ltd.; calcium carbide slag: from Hebei Jiaotong Trunk Material Technology Co., Ltd.; interfacial activator: triethanolamine, industrial grade, 99% content; nanocrystalline nucleating agent: nano CSH nucleating solution, model 510, from Jiangsu Subote New Materials Co., Ltd.; polyvinyl alcohol: brand 1788; nanocellulose: CNF, width 10-50nm, length 0.5-3μm; surfactant: polymerizable surfactant DNS-86, from Guangzhou Double Bond Trading Co., Ltd.

[0047] In the following examples and comparative examples, 1 part is equal to 10 g.

[0048] Embodiment 1: A process for preparing a geopolymer-stabilized recycled aggregate road base material, comprising the following steps:

[0049] Step S1: dissolving 0.2 parts of an interface activator and 0.2 parts of a nanocrystalline nucleating agent in 2.3 parts of water, stirring evenly, to obtain an activator solution, pouring it into 100 parts of brick-concrete recycled aggregate, and soaking it for 2 hours to obtain an impregnated brick-concrete recycled aggregate;

[0050] Step S2: dissolving 0.5 parts of sodium metasilicate pentahydrate, 0.3 parts of sodium silicate and 0.4 parts of sodium hydroxide in 3.45 parts of water to prepare an activator solution;

[0051] Step S3: Add 3 / 10 mass fraction of the activator solution to the soaked brick-concrete recycled aggregate for the first time and mix for 1 minute, then add a mixture of 1.8 parts of fly ash, 1.0 parts of steel slag powder, 1.0 parts of slag powder and 1.0 parts of carbide slag, stir evenly, then add the remaining mass fraction of the activating solution for a second time and mix for 2 minutes to obtain a geopolymer-stabilized recycled aggregate road base material.

[0052] Embodiment 2: A process for preparing a geopolymer-stabilized recycled aggregate road base material, comprising the following steps:

[0053] Step S1: dissolving 0.1 parts of an interfacial activator and 0.2 parts of a nanocrystalline nucleating agent in 2.26 parts of water, stirring evenly, to obtain an activator solution, pouring it into 100 parts of brick-concrete recycled aggregate, and simmering it for 2.5 hours to obtain an impregnated brick-concrete recycled aggregate;

[0054] Step S2: dissolving 0.5 parts of sodium metasilicate pentahydrate, 0.4 parts of sodium silicate and 0.4 parts of sodium hydroxide in 3.39 parts of water to prepare an activator solution;

[0055] Step S3: Add 3 / 10 mass parts of the activator solution to the soaked brick-concrete recycled aggregate for the first time and mix for 2 minutes, then add a mixture of 1.5 parts of fly ash, 1.0 parts of steel slag powder, 2.0 parts of slag powder and 0.5 parts of carbide slag, stir evenly, then add the remaining mass parts of the activating solution for a second time and mix for 3 minutes to obtain a geopolymer stabilized recycled aggregate road base material.

[0056] Embodiment 3: A process for preparing a geopolymer-stabilized recycled aggregate road base material, comprising the following steps:

[0057] Step S1: dissolving 0.1 parts of an interfacial activator and 0.1 parts of a nanocrystalline nucleating agent in 2.32 parts of water, stirring evenly, to obtain an activator solution, pouring it into 100 parts of brick-concrete recycled aggregate, and soaking it for 3 hours to obtain an impregnated brick-concrete recycled aggregate;

[0058] Step S2: dissolving 0.5 parts of sodium metasilicate pentahydrate, 0.4 parts of sodium silicate and 0.6 parts of sodium hydroxide in 3.48 parts of water to prepare an activator solution;

[0059] Step S3: Add 3 / 10 mass fraction of the activator solution to the soaked brick-concrete recycled aggregate for the first time and mix for 3 minutes, then add a mixture of 2 parts of fly ash, 1 part of steel slag powder, 1.5 parts of slag powder and 1 part of carbide slag, stir evenly, then add the remaining mass fraction of the activating solution for a second time and mix for 5 minutes to obtain a geopolymer-stabilized recycled aggregate road base material.

[0060] Example 4: The geopolymer stabilized recycled aggregate road base material includes the following components by weight: 100 parts of brick-concrete recycled aggregate, 1.0 parts of fly ash, 1.5 parts of slag powder, 1.3 parts of steel slag powder, 1.2 parts of carbide slag, 0.5 parts of sodium metasilicate pentahydrate, 0.3 parts of sodium silicate, 0.4 parts of sodium hydroxide, 5.75 parts of water, 0.1 parts of interfacial activator, and 0.15 parts of nanocrystalline nucleating agent; other steps and preparation process are the same as Example 1.

[0061] Example 5: The geopolymer stabilized recycled aggregate road base material includes the following components by weight: 100 parts of brick-concrete recycled aggregate, 2.5 parts of fly ash, 1.5 parts of slag powder, 1.5 parts of steel slag powder, 1.0 parts of carbide slag, 0.8 parts of sodium metasilicate pentahydrate, 0.5 parts of sodium silicate, 0.4 parts of sodium hydroxide, 5.75 parts of water, 0.15 parts of interfacial activator, and 0.3 parts of nanocrystalline nucleating agent; other steps and preparation process are the same as Example 1.

[0062] Example 6: A process for preparing a geopolymer-stabilized recycled aggregate road base material, comprising the following steps:

[0063] Step S1: dissolving 0.05 parts of an interfacial activator and 0.1 parts of a nanocrystalline nucleating agent in 1.8 parts of water, stirring evenly to obtain an activator solution, pouring the solution into the brick-concrete recycled aggregate, and soaking the solution for 2 hours to obtain the impregnated brick-concrete recycled aggregate;

[0064] Step S2: dissolving 0.3 parts of sodium metasilicate pentahydrate, 0.2 parts of sodium silicate and 0.2 parts of sodium hydroxide in 2.7 parts of water to prepare an activator solution;

[0065] Step S3: adding 3 / 10 mass parts of the activator solution to the soaked brick-concrete recycled aggregate for the first time, and stirring for 1 minute, then adding a mixture of 1 part of fly ash, 1.5 parts of steel slag powder, 1 part of slag powder and 0.5 parts of carbide slag, stirring evenly, and then adding the remaining mass parts of the activating solution for a second time for stirring, the mixing time is 2 minutes, and obtaining a geopolymer stabilized recycled aggregate road base material;

[0066] Brick-concrete recycled aggregates are modified, and the specific process is as follows:

[0067] 100 parts of brick-concrete recycled aggregate and silane coupling agent solution are mixed evenly, reacted at 40°C for 2 hours, taken out, added into 300 parts of modified silicone resin, reacted at 30°C for 10 hours, taken out, and air-dried at 100°C for 8 hours to obtain modified brick-concrete recycled aggregate; the silane coupling agent solution includes the following weight components: 10 parts of γ-glycidyloxypropyltrimethoxysilane, 150 parts of ethanol, and 50 parts of deionized water;

[0068] The preparation method of the modified silicone resin is as follows:

[0069] Step A: Under nitrogen protection, 25 parts of octamethylcyclotetrasiloxane, 25 parts of pentamethylpentavinylcyclopentasiloxane and 50 parts of trifluoropropyltrimethylcyclotrisiloxane were mixed evenly, the temperature was raised to 100°C, 0.015 parts of tetramethylammonium hydroxide and 0.05 parts of deionized water were added and mixed evenly, the reaction was continued for 3 hours, the temperature was continued to be raised to 145°C, the temperature was kept for 2 hours, and after filtering and drying, a terminal hydroxyl fluorinated organosilicon was obtained;

[0070] Step B: 50 parts of polyvinyl alcohol and 500 parts of deionized water were mixed uniformly at 80° C., cooled to 60° C., 50 parts of terminal hydroxyl fluorinated silicone and 1.5 parts of dibutyltin dilaurate were added, reacted for 2 hours, filtered and dried to obtain a modified polymer;

[0071] Step C: Under nitrogen protection, 30 parts of nanocellulose are ultrasonically dispersed in an N,N-dimethylacetamide solution containing 5 wt% lithium chloride to obtain a 2 wt% nanocellulose solution, the temperature is raised to 50° C., 60 parts of oleic acid chloride are added, the reaction is carried out for 3 hours, and the modified nanocellulose is obtained after filtering, washing, and freeze-drying;

[0072] Step D: 100 parts of the modified polymer, 150 parts of acrylamide, 100 parts of octadecyl methacrylate, 200 parts of methyl methacrylate, 1000 parts of deionized water and 10 parts of azobisisobutyronitrile are uniformly mixed, and a mixed solution of 30 parts of modified nanocellulose, 450 parts of deionized water and 15 parts of a surfactant is added, and the mixture is reacted at 70° C. for 6 hours to obtain a modified silicone resin.

[0073] Example 7: A process for preparing a geopolymer-stabilized recycled aggregate road base material, comprising the following steps:

[0074] Step S1: dissolving 0.3 parts of an interfacial activator and 0.3 parts of a nanocrystalline nucleating agent in 2.6 parts of water, stirring evenly, to obtain an activator solution, pouring it into 100 parts of brick-concrete recycled aggregate, and soaking it for 3 hours to obtain an impregnated brick-concrete recycled aggregate;

[0075] Step S2: dissolving 1 part of sodium metasilicate pentahydrate, 1.2 parts of sodium silicate and 1 part of sodium hydroxide in 3.9 parts of water to prepare an activator solution;

[0076] Step S3: adding 3 / 10 mass parts of the activator solution to the soaked brick-concrete recycled aggregate for the first time, and stirring for 1 minute, then adding a mixture of 2.5 parts of fly ash, 1.5 parts of steel slag powder, 2 parts of slag powder and 1.5 parts of carbide slag, stirring evenly, and then adding the remaining mass parts of the activating solution for a second time for stirring, the mixing time is 5 minutes, and obtaining a geopolymer stabilized recycled aggregate road base material;

[0077] Brick-concrete recycled aggregates are modified, and the specific process is as follows:

[0078] 100 parts of brick-concrete recycled aggregate and silane coupling agent solution are mixed evenly, reacted at 50°C for 4 hours, taken out, added into 500 parts of modified silicone resin, reacted at 40°C for 12 hours, taken out, and air-dried at 110°C for 10 hours to obtain modified brick-concrete recycled aggregate; the silane coupling agent solution includes the following weight components: 30 parts of γ-glycidyloxypropyltrimethoxysilane, 500 parts of ethanol, and 200 parts of deionized water;

[0079] The preparation method of the modified silicone resin is as follows:

[0080] Step A: Under nitrogen protection, 45 parts of octamethylcyclotetrasiloxane, 54 parts of pentamethylpentavinylcyclopentasiloxane and 99 parts of trifluoropropyltrimethylcyclotrisiloxane were mixed evenly, the temperature was raised to 110°C, 0.04 parts of tetramethylammonium hydroxide and 0.29 parts of deionized water were added and mixed evenly, the reaction was carried out for 5 hours, the temperature was further raised to 150°C, the temperature was kept for 3 hours, and after filtering and drying, a terminal hydroxyl fluorinated organosilicon was obtained;

[0081] Step B: 50 parts of polyvinyl alcohol and 600 parts of deionized water were mixed uniformly at 90° C., cooled to 70° C., 100 parts of terminal hydroxyl fluorinated silicone and 2.5 parts of dibutyltin dilaurate were added, reacted for 4 hours, filtered and dried to obtain a modified polymer;

[0082] Step C: Under nitrogen protection, 50 parts of nanocellulose are ultrasonically dispersed in an N,N-dimethylacetamide solution containing 7 wt % lithium chloride to obtain a 5 wt % nanocellulose solution, the temperature is raised to 60° C., 200 parts of oleic acid chloride are added, the reaction is carried out for 5 hours, and the modified nanocellulose is obtained after filtering, washing, and freeze-drying;

[0083] Step D: 100 parts of the modified polymer, 250 parts of acrylamide, 200 parts of octadecyl methacrylate, 300 parts of methyl methacrylate, 1500 parts of deionized water and 30 parts of azobisisobutyronitrile are uniformly mixed, and a mixed solution of 50 parts of modified nanocellulose, 1500 parts of deionized water and 40 parts of a surfactant is added, and the mixture is reacted at 80° C. for 8 hours to obtain a modified silicone resin.

[0084] Comparative Example 1: A process for preparing cement-stabilized crushed stone, comprising the following steps:

[0085] After adding 50wt% water to the limestone aggregate and mixing, the mixture is simmered for 4 hours, and then PO 42.5 cement and the remaining water are added, mixed evenly and molded into test pieces to obtain cement-stabilized gravel with a cement dosage of 5%; the cement-stabilized gravel includes the following weight components: 100 parts of limestone aggregate, 5.0 parts of PO 42.5 cement, and 5.55 parts of water; the composition ratio of the limestone aggregate is consistent with the synthetic gradation of the brick-concrete recycled aggregate in terms of weight percentage.

[0086] Comparative Example 2: A process for preparing cement-stabilized brick-mix recycled aggregate, comprising the following steps:

[0087] Compared with Comparative Example 1, the limestone aggregate in Comparative Example 2 is replaced with brick-concrete recycled aggregate of the same specification, and the other steps and preparation process are the same as those of Comparative Example 1.

[0088] Comparative Example 3: The geopolymer-stabilized recycled aggregate road base material includes the following components by weight: 100 parts of brick-concrete recycled aggregate, 1.0 parts of fly ash, 1.5 parts of slag powder, 1.3 parts of steel slag powder, 1.2 parts of carbide slag, 5.75 parts of water, 0.1 parts of interfacial activator, and 0.15 parts of nanocrystalline nucleating agent; compared with Example 4, Comparative Example 3 does not add sodium metasilicate pentahydrate, sodium silicate, and sodium hydroxide, and the other steps and preparation process are the same as Example 4.

[0089] Comparative Example 4: A method for preparing a geopolymer-stabilized recycled aggregate road base material, comprising the following steps:

[0090] Step S1: Pour 2.3 parts of water into 100 parts of brick-concrete recycled aggregate, and simmer for 2 hours to obtain soaked brick-concrete recycled aggregate;

[0091] Step S2: dissolving 0.5 parts of sodium metasilicate pentahydrate, 0.3 parts of sodium silicate and 0.4 parts of sodium hydroxide in 3.45 parts of water to prepare an activator solution;

[0092] Step S3: adding a mixture of 1.8 parts of fly ash, 1.0 parts of steel slag powder, 1.0 parts of slag powder and 1.0 parts of carbide slag to the soaked brick-concrete recycled aggregate, stirring evenly, and then adding the stimulating solution prepared in step S2 to mix for 2 minutes to obtain a geopolymer-stabilized recycled aggregate road base material;

[0093] Compared with Example 1, in Comparative Example 4, no interface activator and nanocrystal nucleating agent are added, and the base activator is added once, and the other steps are the same as those of Example 4.

[0094] Comparative Example 5: A process for preparing a geopolymer-stabilized recycled aggregate road base material, comprising the following steps:

[0095] Brick-concrete recycled aggregates are modified, and the specific process is as follows:

[0096] 100 parts of brick-concrete recycled aggregate and silane coupling agent solution were mixed evenly, reacted at 40°C for 2 hours, taken out, and air-dried at 100°C for 8 hours to obtain modified brick-concrete recycled aggregate; the silane coupling agent solution included the following weight components: 10 parts of γ-glycidyloxypropyltrimethoxysilane, 150 parts of ethanol, and 50 parts of deionized water;

[0097] Compared with Example 6, Comparative Example 5 does not include the preparation method of the modified silicone resin, and the other steps are the same as those of Example 6.

[0098] Experiment: Take the geopolymer-stabilized recycled aggregate road base materials obtained in Examples 1-7 and Comparative Examples 3-5, the cement-stabilized crushed stone obtained in Comparative Example 1, and the cement-stabilized brick-concrete recycled aggregate obtained in Comparative Example 2, put them into a vibrating compactor or a press to form test pieces, and then put them into a curing box for curing. After curing to a specified age, samples are prepared and performance tests are carried out.

[0099] Referring to the test method of "Testing Procedures for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTGE-51-2009), the unconfined compressive strength, splitting strength, flexural tensile strength and total shrinkage coefficient of the test specimens were tested. Unconfined compressive strength, splitting strength and flexural tensile strength are commonly used strength indicators for road bases. Among them, the higher the unconfined compressive strength, the stronger the bearing capacity of the material; the higher the splitting strength, the better the crack resistance of the material; the higher the flexural tensile strength, the stronger the ability of the base material to resist bending fracture, and the more difficult it is for the semi-rigid base to fracture under vehicle load; the lower the total shrinkage coefficient, the smaller the shrinkage deformation of the material, and the smaller the risk of shrinkage cracking.

[0100] The test results are as follows:

[0101]

[0102] According to the data in the above table, we can clearly draw the following conclusions:

[0103] 1. By comparing Examples 1-7 with Comparative Example 1, it can be shown that the geopolymer stabilized recycled aggregate road base material prepared by the present invention is similar to cement stabilized crushed stone in terms of unconfined compressive strength, and can meet the compressive strength requirement of 5-7MPa of unconfined compressive strength of extremely heavy-grade highways at 7d, and the bending and tensile capacity also exceeds the 0.9MPa required by the specification, meeting the bearing capacity standard of highways under extremely heavy traffic conditions. At the same time, the splitting strength and bending and tensile strength of the geopolymer stabilized brick-concrete recycled aggregate are slightly higher than those of the cement stabilized crushed stone of Comparative Example 1.

[0104] 2. Compared with Examples 1-7, the compressive strength and splitting strength of Comparative Examples 2-4 are reduced, mainly because there are more impurities on the surface of the brick-concrete recycled aggregate and the interface bonding strength is poor, which makes the mortar-bone interface strength very easy to be damaged and cracked when it is stressed. Therefore, the compressive strength, splitting strength and flexural tensile strength of Comparative Examples 2-4 are relatively low. In particular, the cement-stabilized brick-concrete recycled aggregate of Comparative Example 2 has a drying shrinkage of up to 298×10 -6 , which makes its shrinkage cracking problem particularly serious. In Examples 1-7, by adding interface activators and nanocrystalline nucleating agents, CSH in the cement stone on the surface of brick-concrete recycled aggregate and unreacted cement particles can be effectively activated to produce CSH and CASH hydration products, and the surface of brick-concrete recycled aggregate is modified during the stuffing process, thereby enhancing the compactness of the mortar-bone interface.

[0105] 3. Compared with Examples 6-7, the compressive strength, splitting strength and flexural tensile strength of Example 5 are reduced, indicating that the effect of modifying the brick-concrete recycled aggregate only by using a silane coupling agent (γ-glycidyloxypropyltrimethoxysilane) in the present invention is not as good as the treatment method using a silane coupling agent and a modified silicone resin at the same time.

[0106] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0107] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A geopolymer stabilized recycled aggregate road base material, characterized by: It consists of the following components by weight: 100 parts of brick-concrete recycled aggregate, 1.0-2.5 parts of fly ash, 1.0-2.0 parts of slag powder, 1.0-1.5 parts of steel slag powder, 0.5-1.5 parts of carbide slag, 0.3-1.0 parts of sodium metasilicate pentahydrate, 0.2-1.2 parts of sodium silicate, 0.2-1.0 parts of sodium hydroxide, 4.5-6.5 parts of water, 0.05-0.3 parts of interfacial activator, 0.1-0.3 parts of nanocrystalline nucleating agent; The brick-concrete recycled aggregate is modified, and the specific process is as follows: The brick-concrete recycled aggregate and the silane coupling agent solution are mixed evenly, reacted at 40-50°C for 3-5 hours, taken out, added into the modified silicone resin, reacted at 30-40°C for 10-12 hours, taken out, and air-dried at 100-110°C for 8-10 hours to obtain the modified brick-concrete recycled aggregate; The silane coupling agent solution comprises the following components by weight: 20-30 parts of γ-glycidyloxypropyltrimethoxysilane, 300-500 parts of ethanol, and 100-200 parts of deionized water; The preparation method of the modified silicone resin is as follows: Step A: Under nitrogen protection, octamethylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane and trifluoropropyltrimethylcyclotrisiloxane are mixed evenly, heated to 100-110°C, tetramethylammonium hydroxide and deionized water are added and mixed evenly, reacted for 3-5h, and then heated to 145-150°C, kept warm for 2-3h, filtered and dried to obtain terminal hydroxyl fluorinated organosilicon; Step B: Mix polyvinyl alcohol and deionized water at 80-90° C., cool to 60-70° C., add terminal hydroxyl fluorinated silicone and dibutyltin dilaurate, react for 2-4 hours, filter and dry to obtain a modified polymer; Step C: Under nitrogen protection, ultrasonically dispersing nanocellulose in N,N-dimethylacetamide solution containing lithium chloride to obtain a nanocellulose solution, heating the solution to 50-60° C., adding oleic acid chloride, reacting for 3-5 hours, filtering, washing, and freeze-drying to obtain modified nanocellulose; Step D: uniformly mix the modified polymer, acrylamide, octadecyl methacrylate, methyl methacrylate, deionized water and azobisisobutyronitrile, add a mixed solution of modified nanocellulose, deionized water and a surfactant, and react at 70-80° C. for 6-8 hours to obtain a modified silicone resin.

2. The geopolymer stabilized recycled aggregate road base material according to claim 1, characterized in that: The synthetic gradation of the brick-concrete recycled aggregate is specifically as follows: the percentage passing through the sieve hole size of 19 mm is 100%, the percentage passing through the sieve hole size of 16 mm is 88-93%, the percentage passing through the sieve hole size of 13.2 mm is 76-86%, the percentage passing through the sieve hole size of 9.5 mm is 59-72%, the percentage passing through the sieve hole size of 4.75 mm is 35-45%, the percentage passing through the sieve hole size of 2.36 mm is 22-31%, the percentage passing through the sieve hole size of 1.18 mm is 13-22%, the percentage passing through the sieve hole size of 0.6 mm is 8-15%, the percentage passing through the sieve hole size of 0.3 mm is 5-10%, the percentage passing through the sieve hole size of 0.15 mm is 3-7%, and the percentage passing through the sieve hole size of 0.075 mm is 2-5%.

3. The geopolymer stabilized recycled aggregate road base material according to claim 1, characterized in that: The fly ash is low-calcium secondary fly ash, the total mass of SiO2, Al2O3, and Fe2O3 is not less than 70%, the mass fraction of free calcium oxide is not more than 1.0%, the mass fraction of sulfur trioxide is not more than 3.5%, and the pass rate of 45μm square hole sieve is not less than 70%.

4. The geopolymer stabilized recycled aggregate road base material according to claim 1, characterized in that: The slag powder is S95 grade slag powder.

5. The geopolymer stabilized recycled aggregate road base material according to claim 1, characterized in that: The interface activator is an alcoholamine material, specifically one of triethanolamine, triisopropanolamine, diethanol monoisopropanolamine and monoisopropanolamine.

6. The geopolymer stabilized recycled aggregate road base material according to claim 1, characterized in that: The nano crystal nucleation agent is a nano CSH crystal nucleation solution.

7. A method for preparing a geopolymer-stabilized recycled aggregate road base material according to any one of claims 1 to 6, characterized in that: The steps include: Step S1: dissolving the interface activator and the nanocrystalline nucleating agent in 2 / 5 of the mass fraction of water, stirring evenly to obtain an activator solution, pouring it into the brick-concrete recycled aggregate, and soaking it for 2-3 hours to obtain the impregnated brick-concrete recycled aggregate; Step S2: dissolving sodium metasilicate pentahydrate, sodium silicate and sodium hydroxide in the remaining mass fraction of water to prepare an activator solution; Step S3: Add 3 / 10 mass fraction of activator solution to the soaked brick-concrete recycled aggregate for the first time and mix for 1-3 minutes, then add a mixture of fly ash, steel slag powder, slag powder and carbide slag, stir evenly, and then add the remaining mass fraction of activator solution for a second time and mix for 2-5 minutes to obtain geopolymer stabilized recycled aggregate road base material.

Citation Information

Patent Citations

  • Cementing material for preparing road base material through using brick and concrete building wastes, and application thereof

    CN103274613A

  • Fly ash-mineral powder geopolymer stabilized macadam for pavement base and preparation process of fly ash-mineral powder geopolymer stabilized macadam

    CN115259765A